3D HOLOGRAM OPTICAL ELEMENT FOR ANGLE MEASURING DEVICES AND SIGHTING SYSTEMS - Тюрін, Олександр; Жуков, Сергій; Ахмеров, Олександр (SWorldJournal, 2023)
In this work, a hologram optical element is proposed for optical-electronic angle measuring devices and sighting systems, which is a combination of four three-dimensional diffraction gratings registered in the volume of a photosensitive medium.The method